Mapping the mathematical-logical competencies of graduating students at the end of higher education - Boros József; Борош Йосип; Kuchinka Katalin; Кучінка Каталін; Kucsinka Katalin (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. This research addresses the critical need to benchmark the mathematical-logical competency profiles of graduating higher education students against national and international standards (TIMSS, PISA, AI comparisons). The study's primary objective is to quantitatively map the key components of students' analytical reasoning and problem-solving skills to assess the effectiveness of current curricula and identify targeted areas for educational modernization, specifically focusing on the Transcarpathian region's human capital development. The research aims to map the mathematical-logical competencies of graduating students, identify the main components of their competency profiles, and evaluate the effectiveness of higher education programs. The study is based on the structure of the Hungarian National Competency Assessment [1], the findings of the international TIMSS assessment [2], and the latest OECD analyses examining the comparison between artificial intelligence and human cognitive performance [3]. The research employs a quantitative methodology: an online survey and statistical analysis were used to develop the competency map. The study focuses on students’ mathematical and logical reasoning as well as problem-solving skills. The results are comparable across different study programs and cohorts and can also be analyzed in relation to prior (entry-level) competency data, as proposed in earlier comparative studies [4]. The research is expected to reveal students’ strengths in mathematical reasoning, analytical thinking, and the recognition of logical relationships, while identifying areas for improvement such as digital problem-solving and abstract reasoning. The competency map provides a valuable foundation for modernizing curricula, developing teaching programs, and improving labor market preparedness, thereby strengthening the social and economic stability of young intellectuals in the Transcarpathian region.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: mathematical-logical competency; graduating students